Analysis of the Effect of Variations of Silica Concentration on Synthesis γ-Al2O3 - Fuadiyah, Nadhifatul; Marjunus, Roniyus; Rustyawan, Wawan; Syafriadi, Syafriadi (Departement of Physics, Faculty of Mathematics and Natural Sciences, University of Lampung, 2024)
Research has been carried out to analyze the effect of variations in silica concentration on the synthesis of γ-Al2O3. This research was conducted to determine the variation of Silica against the support γ-Al2O3which is the best as a hydrotreating catalyst in the green fuel industry by using several physical characteristics and analyzing the effect of silica variations on the surface area, pore volume, and pore size of the support. This study uses materials such as Boehmite (AlOOH), equates, 25% NH4OH solution, 6% HNO3, and several variations of Silica such as (Carboxyl, SIRAL, and ZSM). In the process of making supports γ-Al2O3with the sol-gel method in order to homogenize the solutions and silica powders as a buffer variant, it becomes AlOH powder, which is then printed with a press and calcined at a temperature of 550oC gradually to become powder.buffer γ-Al2O3. From the study results, the best variation of γ-Al2O3 silica buffer was carboxyl with a concentration of 6% because several characterization studies showed superior results to γ-Al2O3 support without silica variation. The results of the Surface Area Analyzer characterization greatly affect the hydrotreating catalyst process in the green fuel industry, namely the γ-Al2O3 buffer with the addition of 6% silica carboxyl concentration. This is because a large surface area, pore size, and large pore volume can contain more impregnant solution, and the amount of active phase dispersed will also be greater.